Romania's trade relationship with the European Union in the prospect of joining the euro area - Camelia Milea (Financial Studies, 2019)
The choice of the research topic is due to the national challenge, that the entry of our country into the euro area will have mainly positive consequences for the Romanian economy.The article1presents the evolution of the Romanian current account deficit in relation to the European Union. It can be seen that the degree of commercial integration of our country with the European Union is at a high level, and that the commercial relationship withthe European Union countries is the main cause of Romania's trade deficit.Using qualitativeand quantitative assessments, interpretations and comparative analyses, the article shows that Romania is not in a situation favourable to the economic convergence with the European Union countries in terms of the current account deficit. The analysis is performed for the period 2006-2018, in order to compare the current situation (from 2018) with that in the year before our country entered the European Union.
Keywords: F14; F15; F36; F45; 330; trade relationships; trade deficit; risks; unfavourable situation